2017
DOI: 10.1038/bmt.2017.161
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and severity criteria for sinusoidal obstruction syndrome/veno-occlusive disease in pediatric patients: a new classification from the European society for blood and marrow transplantation

Abstract: The advances in hematopoietic cell transplantation (HCT) over the last decade have led to a transplant-related mortality below 15%. Hepatic sinusoidal obstruction syndrome/veno-occlusive disease (SOS/VOD) is a life-threatening complication of HCT that belongs to a group of diseases increasingly identified as transplant-related, systemic endothelial diseases. In most cases, SOS/VOD resolves within weeks; however, severe SOS/VOD results in multi-organ dysfunction/failure with a mortality rate >80%. A timely diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
374
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 255 publications
(389 citation statements)
references
References 89 publications
9
374
1
5
Order By: Relevance
“…Children differ substantially from adults, with an incidence of VOD/ SOS approximately two-to three-fold higher overall [4,[7][8][9], and rates as high as 30-60% in highrisk subpopulations like infants and those with inherited diseases like familial hemophagocytic lymphohistiocytosis, thalassemia [10] and osteopetrosis [7,11,12]. Clinical presentation also differs in children, who often lack hyperbilirubinemia [4,7,13,14], the hallmark of VOD/SOS. Development of VOD/SOS after HSCT involves a complex pathophysiologic cascade initiated by the toxic injury from the conditioning regimen, with subsequent endothelial-cell damage and activation, and a prothrombotichypofibrinolytic state leading to central venous occlusion and/or sinusoidal obstruction [1,15,16].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Children differ substantially from adults, with an incidence of VOD/ SOS approximately two-to three-fold higher overall [4,[7][8][9], and rates as high as 30-60% in highrisk subpopulations like infants and those with inherited diseases like familial hemophagocytic lymphohistiocytosis, thalassemia [10] and osteopetrosis [7,11,12]. Clinical presentation also differs in children, who often lack hyperbilirubinemia [4,7,13,14], the hallmark of VOD/SOS. Development of VOD/SOS after HSCT involves a complex pathophysiologic cascade initiated by the toxic injury from the conditioning regimen, with subsequent endothelial-cell damage and activation, and a prothrombotichypofibrinolytic state leading to central venous occlusion and/or sinusoidal obstruction [1,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Although regimen-related risk factors are similar in adults and children, the impact of patientrelated risk factors is greater in children than in adults [4]. Both varying presence of risk factors in study populations and use of the Baltimore or modified Seattle criteria for identification and diagnosis of VOD/SOS across studies have contributed to the wide range in VOD/SOS prevalence rates reported in post-HSCT patients [5].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations